2012
DOI: 10.1155/2012/283726
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Connective Tissue Growth Factor in Patients with Nonalcoholic Fatty Liver Disease: Association with Liver Fibrosis

Abstract: Aim:In this study, we aimed to investigate the relationship between the histological fibrosis stage of nonalcoholic fatty liver disease (NAFLD) and serum connective tissue growth factor (CTGF) to determine the usefulness of this relationship in clinical practice.Methods:Serum samples were collected from 51 patients with biopsy-proven NAFLD and 28 healthy controls, and serum levels of CTGF were assayed by ELISA.Results:Levels of CTGF were significantly higher in patients with NAFLD compared with controls (P= 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…CTGF-positive cell number is the best candidate to monitor the disease progress among the selected biochemical, histological and immunostaining parameters, showing a steady increase with comparatively little variance (among top ANOVA results, p adj = 7.9E-10). This is consistent with data from other studies, which observed a correlation of increased CTGF levels with histological fibrosis stages [ 34 , 35 ]. Since CTGF can be measured in patients’ blood, it was suggested as valuable diagnostic marker with potential application in the follow-up of patients suffering from chronic liver diseases [ 36 ].…”
Section: Resultssupporting
confidence: 93%
“…CTGF-positive cell number is the best candidate to monitor the disease progress among the selected biochemical, histological and immunostaining parameters, showing a steady increase with comparatively little variance (among top ANOVA results, p adj = 7.9E-10). This is consistent with data from other studies, which observed a correlation of increased CTGF levels with histological fibrosis stages [ 34 , 35 ]. Since CTGF can be measured in patients’ blood, it was suggested as valuable diagnostic marker with potential application in the follow-up of patients suffering from chronic liver diseases [ 36 ].…”
Section: Resultssupporting
confidence: 93%
“…Nevertheless, this possibility might be verified by a study examining levels of Hsp47 mRNA in liver biopsies at various stages of fibrosis. In addition, a few studies utilized IHC and ELISA (enzyme-linked immunosorbent assay), and revealed that TGF- β 1 and CTGF were up-regulated in hepatic fibrosis induced by hepatitis B virus infection, hepatitis C virus infection and non-alcoholic fatty liver (Kanzler et al 2001; Lu et al 2003; Colak et al 2012). In our opinion, quantitative evaluation of mRNA levels in liver specimens was helpful to investigate their correlation with the progression of CS.…”
Section: Discussionmentioning
confidence: 99%
“…CTGF is a central mediator of TGFβ-dependent fibrogenesis. Expression has been found to be elevated in liver biopsies from NASH patients and serum levels have been found to be positively correlated with fibrosis stage in NAFLD patients, thus underlining a key role in disease and potential application as biomarker [67][68][69]. CTGF is induced by IL-13, supporting a link between chronic inflammatory signaling and the promotion of fibrosis that is possibly independent of TGFβ-induced signaling [44,70].…”
Section: Growth Factorsmentioning
confidence: 94%